Fluctuating epistemic uncertainty in a design team as a metacognitive driver for creative cognitive processes. Issue 2 (3rd April 2018) - Christensen, Bo Thomas; Ball, Linden J.
Abstract: Previous design research has demonstrated how epistemic uncertainty engenders localised, creative reasoning, including analogising and mental simulation. We analysed not just the short-term, localised effects of epistemic uncertainty on creative processing and information selection, but also its long-term impact on downstream creative processes. Our hypothesis was that heightened levels of uncertainty associated with a particular cognitive referent would engender: (1) immediate creative elaboration of that referent aimed at resolving uncertainty and determining information selection; and (2) subsequent attentive returns to that cognitive referent at later points in time, aimed at resolving lingering uncertainty and determining information selection. Findings: First—contrary to expectations—we observed that increased epistemic certainty (rather than increased epistemic uncertainty) in relation to cognitive referents triggered immediate, creative reasoning and information elaboration. Second, epistemic uncertainty was, as predicted, found to engender subsequent attentive returns to cognitive referents. Third, although epistemic uncertainty did not predict the selection of information, both immediate creative elaboration and subsequent attentive returns did predict information selection, with subsequent attentive returns being the stronger predictor. Our findings hold promise for identifying more global impacts of epistemic uncertainty on creative design cognition possibly mediated through the establishment of lasting associations with cognitive referents.